Enrichissement illicite : guide sur les lois ciblant la richesse inexpliquée. (Basel Institute on Governance, 2022)
Illicit Enrichment provides a comprehensive guide to illicit enrichment laws and how to apply them to pursue unexplained assets and recover the proceeds of corruption and other crimes. The book, which is available free of charge, covers criminal and civil laws from around the world. Investigators, prosecutors, lawmakers and academics will benefit from the clear descriptions and practical advice on different approaches to dealing with unexplained increases in wealth, on how to establish cases in court; and on legal challenges common to illicit enrichment laws.